Blueberry Juice Attenuates Pulmonary Fibrosis via Blocking the TGF-β1/Smad Signaling Pathway - Li, Yali; Wang, Liqun; Zhang, Qianyu; Tian, Li; Gan, Cailing; Liu, Hongyao; Yin, Wenya; Ye, Tinghong (Frontiers in Pharmacology, 2022)
Idiopathic pulmonary fibrosis (IPF) is a progressive, fatal and chronic lung disease, lacking a validated and effective therapy. Blueberry has demonstrated multiple pharmacological activities including anti-inflammatory, antioxidant and anti-cancer. Therefore, the objective of this study was to investigate whether blueberry juice (BBJ) could ameliorate IPF. Experiments in vitro revealed that BBJ could significantly reduce the expressions of TGF-β modulated fibrotic protein which were involved in the cascade of fibrosis in NIH/3T3 cells and human pulmonary fibroblasts. In addition, for rat primary lung fibroblasts (RPLF), BBJ promoted the cells apoptosis along with reducing the expressions of α-SMA, Vimentin and Collagen I, while increasing E-Cadherin level. Furthermore, BBJ could reverse epithelial-mesenchymal transition (EMT) phenotypic changes and inhibit cell migration, along with inducing the upregulation of E-cadherin in A549 cells. Compared with the vehicle group, BBJ treatment alleviated ﬁbrotic pathological changes and collagen deposition both in bleomycin-induced prevention and treatment pulmonary fibrosis models. In fibrotic lung tissues, BBJ remarkably suppressed the expressions of Collagen I, α-SMA, vimentin and improved E-cadherin, which may be related to its inhibition of TGF-β1/Smad pathway and anti-inflammation efficacy. Taken together, these findings comprehensively proved that BBJ could effectively prevent and attenuate idiopathic pulmonary fibrosis via suppressing EMT and TGF-β1/Smad signaling pathway.